Effects of Cooling Periods on Equine Semen Characteristics in Al-Zawraa Park - Ahmed, Roa'a N.; Al-Anifj, Ali J.; Mohammed-Rashid, H.M.; Khalaf, Amal H.; Chiad, L.A.; Eessa, A.A. (American Journal of Biomedicine and Pharmacy, 2026)
Chilling stallion semen in equine reproduction prolongs sperm viability and makes artificial insemination easier, cooling causes physiological changes that can impact membrane integrity, acrosome stability, and overall semen quality; monitoring these parameters over time is crucial to comprehending the limits of semen usability during storage. This research aimed to evaluate the time-dependent changes in semen quality of stallions during chilled storage using a Tris-hydroxymethyl-aminomethan based extender at Al-Zawraa Park, Baghdad. Twelve semen samples were collected from two stallions from October 2024 to April 2025. Ejaculates were collected, diluted, and stored at 5 °C for five consecutive days. Daily assessments included sperm viability, morphological abnormalities, plasma membrane integrity (HOST), and acrosomal status; the results demonstrated a progressive decline in semen quality over time. On day 1, semen samples showed high viability with minimal abnormalities, while plasma membrane and acrosomal structures were well preserved. From day 2 to day 3, a marked reduction in membrane integrity was observed accompanied by increasing morphological defects. By day 5, viability had dropped markedly, membrane integrity was severely impaired, and acrosomal status revealed limited fertilization potential. These findings confirm that cold storage, even with the protective effect of Tris extender, leads to cumulative structural and functional damage in spermatozoa. Stallion semen preserved at 5 °C with Tris-hydroxymethyl-aminomethan extender maintains acceptable quality only for a limited period, with substantial decline beyond 48–72 hours. This research highlights the importance of functional assays such as HOST and acrosomal evaluation for predicting fertility potential and suggests that extender modification or antioxidant supplementation may be required to prolong semen usability.